Together where we are : associational life in a small rural town - Dagson, Simon (SLU/Dept. of Urban and Rural Development, 2017)
Associations and other civil society organisations are active and present in most rural areas of Sweden, and the tradition of associational life is strong. The variation among the associations is large, varying in size and level of activity as well as the goals with the invested engagement. I will investigate the associational life in the local community of a small town to further discuss the role and structure of the civil society organisations in a rural context of a small town. This study investigates the varying forms and motivations existing within the civil society organisations in Malmbäck, and how they relate to the town and those who live in it. The theoretical concept of community has been used as an analytical tool to understand the qualitative empirical material, based on interviews and observations. Beyond the different core interests that the associations are based upon, there are activities with a clear social function where the whole community get together. In the social interaction created by the associations’ activities, experiences and memories are shared and a sense of belonging is created and maintained. The role kept by the civil society organisations in this case, appears to be centred around the local community itself and the sense of belonging. This aspect of civil society differs to other views of rural associations, hence highlighting the variety of the civil society organisations and the need for a nuanced discussion.